QUALITY OF LIFE AND WELL-BEING OF POPULATION AT THE END OF THIRD PHASE OF LOCKDOWN IN INDIA AGAINST THE COVID-19 PANDEMIC - Rathi, H.; Biyani, M.; Malik, M.; Rathi, P. (International Journal of Medicine and Medical Research, 2021)
Background. On March 24, 2020, a nationwide Lockdown for 21 days was ordered by the Government of India which was then extended till May 31, 2020. Researchers have predicted lockdown is a necessary step to prevent COVID-19 spread. However, others have also stated that it could cause serious damage to the economic, mental, social, and physical well-being of the people. Objective. The aim of the study is to evaluate the impact of lockdown on the quality of life and well-being of the Indians. Methods. It is a cross sectional prospective web-based questionnaire study. A link (https://forms.gle/pX25VuahP5NxT88QA) was created. Total 426 responses were received via that link and the data was included in the statistical analysis. Results. Our study revealed that during the lockdown 61.5% of the respondents were performing physical activities lesser than before. More than half responded they had a reduced financial satisfaction. Most answers on emotional well-being and social-family wellbeing were also positive, but some responses showed disturbing too, like 22% felt anxious and nervous over half of the days. It was found in the study that physical, financial, emotional, mental, social and family wellbeing were disturbed during the lockdown and quality of life was also hampered. Conclusion. Though, may be Nationwide Lockdown was the most required action at that point of time to prevent virus spread, but our study revealed that uncertainty regarding its cure and management guidelines like lockdown and social distancing has badly affected quality of life and wellbeing of the population.